Hardiness in relation to organisational commitment in the Human Resource Management field - Nadia Ferreira (SA Journal of Human Resource Management, 2012)
Orientation: Employees’ hardiness is increasingly recognised as an aspect of their well-being and feelings of career success. Psychological well-being and feelings of subjective career success have positive implications for the motivation, satisfaction, performance and commitment of young talented staff. Research purpose: The study empirically investigated the relationship between an individual’s hardiness (measured by the Personal Views Survey II [PVS-II]) and organisational commitment (measured by the Organisational Commitment Scale). Motivation for the study: Research on an individual’s hardiness profile as an aspect of their career well-being and success and how these attributes influence their psychological attachment to the organisation, is needed to guide human resource career development support practices aimed at retaining valuable staff. Research design, approach and method: A quantitative survey was conducted on a convenience sample of predominantly Black (92.2%) and female (71%) employed adults (N = 355) at managerial and staff levels in the human resource management field. Main findings: Correlational and multiple regression analyses revealed a number of significant relationships between the two variables. Practical/managerial implications: Managers and human resource practitioners need to recognise how people’s hardiness relates to their sense of psychological attachment to the organisation. Organisations concerned with the retention and well-being of their equity staff members need to find a way to enhance and develop their hardiness and commitment. Contribution/value-add: The research contributes new insights into and knowledge of the factors that influence their employees’ hardiness and how these relate to their organisational commitment. The results may be used to inform career development support interventions that aim to increase employees’ sense of career well-being and success.